2021
DOI: 10.1016/j.dhjo.2020.101014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on people with physical disabilities: A rapid review

Abstract: Background The COVID-19 pandemic caused drastic changes in the lives of the general population. People with physical disabilities, who commonly encounter daily challenges such as barriers to community mobility, reduced access to healthcare services and higher risk of suffering from depression, may face additional challenges in the context of the pandemic. Objective This study aims to review the impact of the COVID-19 pandemic, and associated isolation and protective mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
138
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(176 citation statements)
references
References 51 publications
12
138
0
13
Order By: Relevance
“…[4][5][6] People with physical disabilities might be at particular risk of adverse mental health and reduced social contact. [7][8][9] Rates of physical disability increase with age, with about a third of adults aged 60 years and older in high-income countries living with a disability. 10 Even before the COVID-19 pandemic, this group faced chal lenges in terms of mobility, access to health-care services, and social contact, and had more emotional distress, a higher risk of loneliness, and a poorer health-related quality of life than people without a physical disability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] People with physical disabilities might be at particular risk of adverse mental health and reduced social contact. [7][8][9] Rates of physical disability increase with age, with about a third of adults aged 60 years and older in high-income countries living with a disability. 10 Even before the COVID-19 pandemic, this group faced chal lenges in terms of mobility, access to health-care services, and social contact, and had more emotional distress, a higher risk of loneliness, and a poorer health-related quality of life than people without a physical disability.…”
Section: Introductionmentioning
confidence: 99%
“…14 A rapid review of studies of people with stroke, multiple sclerosis, chronic pain, and other conditions indicated that most studies focused on access to care, were cross-sectional, and did not involve standardised measures of mental health. 8 One longitudinal study assessed 67 people with multiple sclerosis 6 months before and then during the early weeks of the COVID-19 pandemic in Italy and showed no changes in symptoms of anxiety and depres sion across the two timepoints. 15 This finding led the authors to suggest that people with multiple sclerosis were particu larly resilient; however, this study did not include a comparison group of people without multiple sclerosis, making it difficult to confirm this conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…The speed of the COVID 19 vaccine development was [ 8 ]. Despite some critical notes [ 9 , 10 ], a few anti-COVID-19 vaccines were approved, and public vaccination procedure have been started. At the same time, various pharmaceuticals compounds against coronavirus infection are still being tested and yet to demonstrate their significantly high efficacy rates over placebo as well as lower mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Health and rehabilitation access might also have decreased, partly because non-urgent appointments were postponed or went online, and partly because people became too fearful to go to the doctor. 5 Across Europe, an estimated 1•3-2•2 million people were not receiving the rehabilitation care that they needed each day because of reductions in services in the early months of the pandemic. 6 The consequences will be more pronounced for people with disabilities, who are more likely to need regular health care.…”
Section: Are Older People With Disabilities Neglected In the Covid-19mentioning
confidence: 99%